PENTINGNYA PERAN PROGRAM PERSIAPAN PENSIUN TERHADAP KESIAPAN PENSIUN KARYAWAN - Bun Norikun (LPPM Politeknik Pratama, 2024)
This study is to determine the importance of the role of retirement preparation programs on employee retirement preparation. Retirement is the termination of employees carried out by companies or organizations on employees who have reached an age that is considered no longer productive or which is the standard age limit in the company based on statutory regulations. The problem that often occurs is the unpreparedness of employees to accept the reality of retirement and increased anxiety in employees. In this study with a qualitative method with five respondents who have been interviewed and it is known that 60% of respondents have anxiety in facing retirement which is divided into a light scale of 40% and 20% heavy scale. As well as employees who have prepared for retirement even though only partially or have tried to reach 80%. Based on the results of the retirement program that has been run by the Company, namely that the retirement preparation program is very important for employees who will enter retirement and has a positive and significant influence on retirement readiness and the retirement preparation program will have an influence on the level of employee anxiety, the higher the pre-retirement training and provision, the lower the level of anxiety. The level of employee anxiety greatly affects the level of retirement readiness, the lower the level of anxiety in accepting retirement, the higher the level of employee retirement readiness